Two new species of planthoppers from India (Hemiptera: Auchenorrhyncha: Delphacidae) in the genera Parasogata and Eoeurysa - Ramya, N; Bartlett, Charles; Meshram, Naresh M. (European Journal of Taxonomy, 2020)
The genus Parasogata Zhou, Yang & Chen, 2018 is here reported from India represented by the new species Parasogata sexpartita sp. nov. collected in a recent exploration and survey of delphacids from Nagaland in northeastern India. A second species of Eoeurysa Muir, 1913 from India, the new species Eoeurysa sagittaria sp. nov., was found in Rampur, Una, Himachal Pradesh. Both new species are described with illustrations, and a molecular identification is given with the mtCOI gene sequence. A modified key to species of the genera is also provided.